Good procurement governance and organisational performance: A contingency theory approach to procurement practices in XYZ universities - Sutawijaya, Adrian; Muktiyanto, Ali; Geraldina, Ira; Narimawati, Umi (Journal of Accounting and Investment, 2026)
Research aims: This study examines the effect of Good Procurement Governance (GPG) on organisational performance in public institutions, particularly in XYZ Universities.Design/Methodology/Approach: The research method used quantitative data from a survey of 157 procurement practitioners at the XYZ University, which were analysed statistically using Structural Equation Modelling–Partial Least Squares (SEM-PLS). To complement and deepen the interpretation of the confirmatory factor analysis results, a qualitative approach was subsequently employed through Focus Group Discussions (FGDs) with XYZ University procurement actors.Research findings: The results show that GPG negatively affects organisational performance, while each GPG dimension positively enhances it. This result indicates the importance of fit between regulations, institutions, human resources, and information systems within the contingency theory framework.Theoretical contribution/Originality: This study contributes theoretically by expanding the GPG model grounded in contingency theory and practically by providing recommendations for strengthening procurement governance in public universities.